AMELIORATION OF ALUMINUM- AND FLUORIDE-INDUCED BEHAVIORAL ALTERATIONS THROUGH RESVERATROL IN RATS. - Reddy Nallagouni, Chandra Shakar; Mesram, Nageshwar; Karnati, Pratap Reddy (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The objective of the study was to investigate the ameliorative effects of resveratrol against aluminum- and fluoride-altered neurobehavioral activities. Methods: Aluminum chloride (100 mg/kg body weight [bw])+sodium fluoride (10 mg/kg bw), aluminum chloride (100 mg/kg bw) + sodium fluoride (10 mg/kg bw) + resveratrol (30 mg/kg bw), and resveratrol (30 mg/kg bw) alone were given orally to II, III, and IV groups, respectively, and Group-I was served as control for 8 weeks. The bw, brain weight, grip strength, learning ability, and behavioral activities were assayed. Results: The results showed significantly (*p<0.05) altered body and brain weights, learning ability, grip strength, and behavioral activities in Group- II, whereas significant (*p<0.05) reversal was observed in Group-III. Conclusion: Taken together, the above findings conclude that resveratrol ameliorated aluminum and fluoride-altered neurobehavioral activities.